2018
DOI: 10.2196/11234
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial TheraSphere Yttrium-90 Glass Microspheres in the Treatment of Patients With Unresectable Hepatocellular Carcinoma: Protocol for the STOP-HCC Phase 3 Randomized Controlled Trial

Abstract: BackgroundGlobally, hepatocellular carcinoma is the second most common cause of cancer deaths. It remains challenging to intensify cancer treatment without impairing liver function.ObjectiveThe objective of the TheraSphere in the Treatment of Patients with Unresectable Hepatocellular Carcinoma (STOP-HCC) study is to examine the hypothesis that transarterial radioembolization (TheraSphere yttrium-90 glass microspheres) combined with standard first-line treatment with sorafenib will improve outcomes over treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…Another phase 3 prospective study, the TheraSphere in the Treatment of Patients with Unresectable Hepatocellular Carcinoma (STOP-HCC trial, NCT01556490), that comprises a larger sample size that aimed to detect a difference in the overall survival between the combined therapy and sorafenib alone therapy in unresectable HCC is ongoing, and preliminary results of the two first interim analyses support the continuation of the study. 20 Safety analyses in the SORAMIC study reported higher incidence of grade 3-4 adverse events in the combination therapy group than in the sorafenib only group. 13 Grade 2 adverse events with HFSR were developed in this case, and the patient refused further sorafenib treatment after achieving radiological CR.…”
Section: Discussionmentioning
confidence: 98%
“…Another phase 3 prospective study, the TheraSphere in the Treatment of Patients with Unresectable Hepatocellular Carcinoma (STOP-HCC trial, NCT01556490), that comprises a larger sample size that aimed to detect a difference in the overall survival between the combined therapy and sorafenib alone therapy in unresectable HCC is ongoing, and preliminary results of the two first interim analyses support the continuation of the study. 20 Safety analyses in the SORAMIC study reported higher incidence of grade 3-4 adverse events in the combination therapy group than in the sorafenib only group. 13 Grade 2 adverse events with HFSR were developed in this case, and the patient refused further sorafenib treatment after achieving radiological CR.…”
Section: Discussionmentioning
confidence: 98%
“…In attendance of the results from the ongoing STOP-HCC trial, conducted by the same American group [27], our study represents the first series comparing the two treatment approaches and reporting long-term survival and progression outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, also institutes where the 99m Tc‐MAA scan is used to assess the perfusion of target lesions (with potential necrotic cores) and the activity to the parenchyma. Furthermore, the potential for the 99m Tc‐MAA scan to be used for dosimetry planning is being investigated within trials 13,14 . Our algorithm does not take such (intrahepatic) measures into account and hence should be modified if the above methods are introduced in regular clinical practice.…”
Section: Discussionmentioning
confidence: 99%